High quality hybrid perovskite semiconductor thin films with remarkably enhanced luminescence and defect suppression via quaternary alkyl ammonium salt based treatment - Naphade, Rounak A.; Zhao, Baodan; Richter, Johannes M.; Booker, Edward; Krishnamurthy, Shrreya; Friend, Richard H.; Sadhanala, Aditya; Ogale, Satishchandra B. (Advanced Materials Interfaces, 2017)
Significant enhancement in the luminescence and superior photophysical properties of CH3NH3PbBr3 thin films prepared via simple single step spin coating process involving a novel additive mediated solvent extraction step is reported. This process results in significantly lower disorder in CH3NH3PbBr3 perovskites with Urbach energies reducing from ≈35 to ≈17 meV, which is the lowest reported value to date. The additive mediated process also results in a remarkable improvement in the photoluminescence quantum yields (PLQYs) from 1% to 30%. Coupled with the overall increase in surface roughness, a significant increase in the internal PLQY from 7% to 77% is estimated, indicating the superior quality of the treated thin films. The resultant high quality CH3NH3PbBr3 perovskites with remarkable photophysical properties can be used in realizing highly efficient optoelectronic devices. Highly efficient light emitting diodes using these perovskites are demonstrated here.

Phenothiazine-based D-A-π-A dyes for highly efficient dye sensitized solar cells: effect of internal acceptor and non-conjugated π-spacer on device performance - Nagane, Satyawan; Ichake, Amol; Agrawal, Ishita; Sadhanala, Aditya; Friend, Richard H.; Ogale, Satishchandra; Wadgaonkar, Prakash P. (ChemPlusChem, 2017)
Three new D-A-pi-A metal-free organic dyes based on phenothiazine as a donor (D) and non-conjugated pi-spacer were designed and synthesized. The incorporation of different 'internal acceptors' (electron traps) such as benzothiadiazole (BTD), benzotriazole (BTA), and pyridine were shown to allow systematic tuning of the energy levels and the photophysical properties. The AI-1 dye showed lower electronic disorder compared with the other two dyes. The efficiencies achieved with AI-1, AI-2, and AI-3 dyes were 8.5% (J(sc) = 15.42 mA cm(-2), V-oc = 0.78 V, FF = 68%), 7% (J(sc) = 12.8 mA cm(-2), V-oc = 0.78 V, FF = 68%) and 6.7% (J(sc) = 11.57 mA cm(-2), V-oc = 0.82 V, FF = 68.26 %), respectively. The incorporation of non-conjugated phenothiazine as a p-spacer in D-A-pi-A dyes showed remarkable enhancement in the photovoltaic performance of dye-sensitized solar cell (DSSC) devices. The sealed DSSC devices with iodide/tri-iodide (I-/I-3(-) @)based liquid electrolyte showed promising stability under ambient conditions.